Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Otherwise: imagining queer feminist art histories - Jones, Amelia; Silver, Erin (Manchester University Press, 2016)
Otherwise: Imagining queer feminist art histories" is the first publication to address queer feminist politics, methods and theories in relation to the visual arts, including new media, installation and performance art. Despite the crucial contribution of considerations of 'queer' to feminism in other disciplines of the humanities, and the strong impact of feminist art history on queer visual theory, a visible and influential queer feminist art history has remained elusive. This book fills the gap by offering a range of essays by key North American and European scholars, both emerging and renowned, who address the historiographic and political questions arising from the relationship between art history and queer theory in order to help map exclusions and to offer models of a new queer feminist art historical or curatorial approach.
Keywords: LGBTQIA2+; amérique du nord; amériques; approches et analyses; art contemporain; arts; arts visuels et médiatiques; cours; discipline; europe; har4600; histoire de l'art; identités LGBTQIA2+; installation; performance; premier cycle; queer; régions géographiques; thématiques; transféminisme